Impact of immature platelets on platelet response to ticagrelor and prasugrel in patients with acute coronary syndrome - Bernlochner, Isabell; Goedel, Alexander; Plischke, Conny; Schuepke, Stefanie; Haller, Bernhard; Schulz, Christoph; Mayer, Katharina; Morath, Tanja; Braun, Siegmund; Schunkert, Heribert; Siess, Wolfgang; Kastrati, Adnan; et al. (European Heart Journal, 2015)
Aims The influence of reticulated platelets (RPs) on platelet inhibition by ticagrelor when compared with prasugrel is unknown. We aimed to determine the influence of RPs on adenosine diphosphate-(ADP-) induced platelet aggregation in patients with acute coronary syndrome who were randomly assigned to receive either ticagrelor or prasugrel for P2Y12 receptor inhibition. Met hods and resul ts One hundred and twenty-four patients were prospectively enrolled. The immature platelet fraction (IPF) was measured by an automated haematoanalyzer and platelet aggregation was assessed by multiple electrode aggregometry. In a subgroup of patients (n = 28) ADP-induced P-selectin expression was measured in dependence of the time point of study drug intake in RPs that were discriminated from mature platelets by thiazole-orange (TO) staining. The primary endpoint was the correlation of platelet aggregation and IPF in ticagrelor-vs. prasugrel-treated patients. Platelet aggregation significantly correlated with IPF in patients who received prasugrel (r = 0.41, P, 0.001). In contrast, no correlation between IPF and platelet aggregation was observed in ticagrelor-treated patients (r = 0.08, P = 0.51, P for difference of correlation coefficients P = 0.05). Within the TO-positive RP fraction, P-selectin expression was significantly higher in prasugrel when compared with ticagrelor-treated individuals (prasugrel 18.6 + 16.0% vs. ticagrelor 11.5 + 6.0%, P = 0.047). A time-dependent P-selectin expression was observed in prasugrel but not in ticagrelortreated patients (prasugrel early 11.9 + 9.4% vs. late 26.3 + 19.0%, P = 0.031, ticagrelor early 9.6 + 4.9% vs. late 13.5 + 6.6%, P = 0.127). Conclusion Reticulated platelets show a greater impact on platelet reactivity in response to prasugrel when compared with ticagrelor.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Reticulated platelets † Platelet aggregation † Ticagrelor † Prasugrel † Acute coronary syndrome